Incompatible erythrocyte transfusion with lipopolysaccharide induces acute lung injury in a novel rat model - Gregory Rivera, Magdielis; Sampson, Alana C.; Hair, Pamela S.; Pallera, Haree K.; Jackson, Kaitlyn G.; Enos, Adrianne I.; Vazifedan, Turaj; Werner, Alice L.; Goldberg, Corinne L.; Lattanzio, Frank A.; Cunnion, Kenji M.; Krishna, Neel K. (PloS one, 2020)
Acute transfusion reactions can manifest in many forms including acute hemolytic transfusion reaction, allergic reaction and transfusion-related acute lung injury. We previously developed an acute hemolytic transfusion reaction rat model mediated by transfusion of incompatible human erythrocytes against which rats have preexisting antibodies resulting in classical complement pathway mediated intravascular hemolysis. In this study, the acute hemolytic transfusion reaction model was adapted to yield an acute lung injury phenotype. Adolescent male Wistar rats were primed in the presence or absence of lipopolysaccharide followed by transfusion of incompatible erythrocytes. Blood was collected at various time points during the course of the experiment to determine complement C5a levels and free DNA in isolated plasma. At 4 hours, blood and lung tissue were recovered and assayed for complete blood count and histological acute lung injury, respectively. Compared to sham animals or animals receiving increasing amounts of incompatible erythrocytes (equivalent to a 15-45% transfusion) in the absence of lipopolysaccharide, lungs of animals receiving lipopolysaccharide and a 30% erythrocyte transfusion showed dramatic alveolar wall thickening due to neutrophil infiltration. C5a levels were significantly elevated in these animals indicating that complement activation contributes to lung damage. Additionally, these animals demonstrated a significant increase of free DNA in the blood over time suggestive of neutrophil extracellular trap formation previously associated with transfusion-related acute lung injury in humans and mice. This novel 'two-hit' model utilizing incompatible erythrocyte transfusion in the presence of lipopolysaccharide yields a robust acute lung injury phenotype.